PERTANGGUNG JAWABAN PIDANA KELALAIAN DALAM LALU LINTAS OLEH ANAK YANG MENYEBABKAN ORANG LAIN MENINGGAL DUNIA - Lastarida Br Sitanggang; Surya Perdana (JURNAL DOKTRIN REVIEW, 2022)
Traffic accidents involving children as perpetrators tend to be due to a lack of parental supervision of their children in giving permission to drive a motor vehicle, resulting in a traffic accident, then the child as a traffic accident criminal, to find out the criminal responsibility for negligence in traffic by children who cause others to die. Traffic accidents in general were previously regulated in Articles 359, 360, 361 of the Criminal Code and specifically regulated in Law Number: 22 of 2009 concerning Road Traffic and Transportation (UULLDAJ). In the event of a traffic accident, the legal provisions that must be applied are referring to UULLDAJ. And efforts to resolve legal problems against children who commit negligence in traffic by applying Article 6 of the UUSPPA, then diversion as an implementation of restorative justice seeks to restore recovery to a problem, by solving it outside the court by involving perpetrators, victims, families, and related parties. , for a diversion solution. Obstacles in implementing diversion, namely the lack of internal law enforcers who know about diversion; lack of facilities and amenities; minimal diversion time limit; difficulty summoning the parties; the external constraints of the parties are not present in the diversion process; there are parties who are not willing to make peace; victim's request; children do not want to be responsible; does not implement the results of the diversion.